A novel chemiluminescence enhanced method for determination of putrescine in shrimp based on the luminol–[Ag(HIO6)2]5− reaction. Issue 5 (14th January 2016) - Chen, Peiyun; Sun, Hanwen; Wang, Xianyou; Pang, Yanping; Li, Bin
Abstract : A novel chemiluminescence enhanced method for the determination of putrescine in shrimp based on the luminol–[Ag(HIO6 )2 ] 5− reaction. Abstract : A novel chemiluminescence (CL) method to determine putrescine was proposed based on the enhanced effect of putrescine on CL emission of the [Ag(HIO6 )2 ] 5− –luminol system. The enhanced degree of CL emission was proportional to the putrescine concentration. Under optimal conditions, there was a linear relationship between the increase in CL intensity and the putrescine concentration over a range of 4.0 × 10 −8 to 4 × 10 −6 g mL with a detection limit (3 σ ) of 1.76 × 10 −8 g mL −1 . The relative standard deviation (RSD) was 3.2% for 11 replicate determinations of 1.0 × 10 −6 g mL −1 putrescine. The proposed CL reaction systems had potential capability for residue analysis of studied analytes in food samples. A possible mechanism of CL emission and enhanced effect was also suggested.